DARI TRANSPARANSI MENUJU OPTIMALISASI ANALISIS MANAJEMEN KEUANGAN DAN SARANA PRASARANA DI SD IT DARUL ABROR - Shindy Aulia Zahra; Ejen Jenal Mutaqin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of financial resources and educational facilities at SD IT Darul Abror, identify factors that hinder the optimization of resource management in schools, and examine efforts made to overcome these obstacles. This research employs a qualitative method using a literature study approach. The data were obtained from various relevant sources such as books, scientific journals, research articles, and academic documents related to educational financial management and school facilities management. Data collection techniques were carried out through documentation studies and literature analysis, while the data analysis technique used content analysis to examine various concepts, theories, and findings from previous studies. The results of the study indicate that transparency in school financial management is an important principle in improving accountability and building trust among stakeholders. However, transparency alone is not sufficient to ensure the optimal management of educational resources without being supported by an effective and efficient management system. Effective management of educational facilities includes planning, procurement, inventory, utilization, maintenance, and supervision carried out continuously. Furthermore, several factors hinder the optimization of resource management in schools, including limited financial resources, lack of managerial competence among school administrators, weak monitoring and evaluation systems, and limited stakeholder participation in school management. Therefore, strategic efforts are needed to improve budget planning, strengthen human resource competence, implement effective supervision and evaluation systems, and enhance stakeholder participation in school management. These efforts are expected to support the optimization of financial and facilities management in schools in a more effective and sustainable manner.